New delay-dependent robust stability criterion for lpd discrete-time systems with interval time-varying delays - Yotha N. (2014)
This paper investigates the problem of robust stability for linear parameter-dependent (LPD) discrete-time systems with interval time-varying delays. Based on the combination of model transformation, utilization of zero equation, and parameter-dependent Lyapunov-Krasovskii functional, new delay-dependent robust stability conditions are obtained and formulated in terms of linear matrix inequalities (LMIs). Numerical examples are given to demonstrate the effectiveness and less conservativeness of the proposed methods. © 2013 Narongsak Yotha and Kanit Mukdasai.